Delayed effects and complex life cycles: How the larval aquatic environment influences terrestrial performance and survival. (23rd August 2018) - Rumrill, Caitlin T.; Scott, David E.; Lance, Stacey L.
Abstract: Species with complex life cycles are susceptible to environmental stressors across life stages, but the carryover and latent effects between stages remain understudied. For species with biphasic life histories, such as pond‐breeding amphibians, delayed effects of aquatic conditions can influence terrestrial juveniles and adults directly or indirectly, usually mediated through fitness correlates such as body size. We collected adult southern toads ( Anaxyrus terrestris ) from 2 source populations—a natural reference wetland and a metal‐contaminated industrial wetland—and exposed their offspring to 2 aquatic stressors (a metal contaminant, copper [Cu], and a dragonfly predator cue) in outdoor mesocosms ( n = 24). We then reared metamorphs in terraria for 5 mo to examine delayed effects of early life stage environmental conditions on juvenile performance, growth, and survival. Larval exposure to Cu, as well as having parents from a contaminated wetland, resulted in smaller size at metamorphosis—a response later negated by compensatory growth. Although Cu exposure and parental source did not affect larval survival, we observed latent effects of these stressors on juvenile survival, with elevated Cu conditions and metal‐contaminated parents reducing postmetamorphic survival. Parental source and larval Cu exposure affected performance at metamorphosis through carryover effects on body size but, 1 mo later, latent effects of parental source and larval predator exposure directly (i.e., not via body size) influenced performance. The carryover and latent effects of parental source population and aquatic Cu level on postmetamorphic survival and juvenile performance highlight the importance of conducting studies across life stages and generations. Environ Toxicol Chem 2018;37:2660–2669. © 2018 SETAC